Reexamining emerging market animosity toward western developed countries: A social dilemma in physical retailing consumption under normative influence - Fong, Cher-Min; Chang, Hsing-Hua Stella; Lin, Mong-Ching; Chen, I-Hung (Journal of retailing and consumer services, 2022)
Focusing on physical retailing as an apparent target for boycotts in the context of emerging market consumers' animosity toward Western developed countries, this research pioneers in its in-depth examination of a social dilemma whereby consumers on one hand wish to avoid purchasing Western products/services to meet social expectations, while on the other wish to continue purchasing Western products/services, because of perceived Western product/service superiority, at the risk of social disapproval. Differing from conventional animosity research that largely neglects interpersonal influence, this research synthesizes social influence theory and social exchange theory to compare consumers’ purchase decisions in visible (physical retailing) and less-visible (online shopping) consumption contexts that are subject to different strengths of normative influence, and proposes a cost-benefit analysis to explain how consumers make trade-offs between social expectations and self-interest. Two studies were conducted to test the hypotheses. Our study findings have important implications for future animosity research on consumer services that are subject to stronger normative pressure. •Stronger (weaker) normative influence led to a higher (lower) level of purchase avoidance/boycotting in physical retailers, but not in less-visible channels.●Normative influence mediated the relationship between animosity attitudes and purchase avoidance/boycott in physical retailers, but not in less-visible channels.●Stronger (weaker) Western product/service superiority led to a lower (higher) level of purchase avoidance/boycott in physical retailing.●Western product/service superiority moderated the effect of perceived normative pressure (anticipated social punishments) on purchase avoidance/boycott in physical retailing.